Systems of nominal classification. - Senft, Gunter (Language, culture, and cognition ;, 2010)
This volume addresses the fundamental linguistic question of how the perceived world is expressed through systems of nominal classification. Leading scholars review the whole spectrum of nominal classification, from gender systems through to numeral classifiers, providing cutting-edge theoretical interpretations and empirical case studies across a variety of languages. The volume presents new ideas about the problems of classification and clarifies the interface between anthropological and grammatical work. It will appeal to linguists, anthropologists and psychologists alike as well as specialists in languages as diverse as Australian, Amazonian, Mayan and Japanese -- Présentation de l'éditeur.